Structuring General and Complete Quantum Computations in Haskell: The Arrows Approach - Vizzotto, Juliana Kaizer; Costa, Antônio Carlos da Rocha; Sabry, Amr (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2007: Anais do XX Concurso de Teses e Dissertações, 2007)
In this thesis we argue that a realistic model for quantum computations should be general with respect to measurements, and complete with respect to the information flow between the quantum and classical worlds. We thus structure general and complete quantum programming in Haskell using well known constructions from classical semantics and programming languages, like monads and arrows. The result connects “generic” and “complete” quantum features to well-founded semantics constructions and programming languages.